Hybrid gelatin/oxidized chondroitin sulfate hydrogels incorporating bioactive glass nanoparticles with enhanced mechanical properties, mineralization, and osteogenic differentiation - Zhou, Lei; Fan, Lei; Zhang, Feng Miao; Jiang, Yuhe; Cai, Min; Dai, Cong; Luo, Yi An; Tu, Ling Jie; Zhou, Zheng Nan; Li, Xiao Jun; Ning, Cheng Yun; Zheng, Kai; et al. (Bioactive Materials, 2021)
Biopolymer based hydrogels are characteristic of their biocompatibility and capability of mimicking extracellular matrix structure to support cellular behavior. However, these hydrogels suffer from low mechanical properties, uncontrolled degradation, and insufficient osteogenic activity, which limits their applications in bone regeneration. In this study, we developed hybrid gelatin (Gel)/oxidized chondroitin sulfate (OCS) hydrogels that incorporated mesoporous bioactive glass nanoparticles (MBGNs) as bioactive fillers for bone regeneration. Gel-OCS hydrogels could be self-crosslinked in situ under physiological conditions in the presence of borax. The incorporation of MBGNs enhanced the crosslinking and accelerated the gelation. The gelation time decreased with increasing the concentration of MBGNs added. Incorporation of MBGNs in the hydrogels significantly improved the mechanical properties in terms of enhanced storage modulus and compressive strength. The injectability of the hydrogels was not significantly affected by the MBGN incorporation. Also, the proliferation and osteogenic differentiation of rat bone marrow mesenchymal stem cells in vitro and rat cranial defect restoration in vivo were significantly promoted by the hydrogels in the presence of MBGNs. The hybrid Gel-OCS/MBGN hydrogels show promising potential as injectable biomaterials or scaffolds for bone regeneration/repair applications given their tunable degradation and gelation behavior as well as favorable mechanical behavior and osteogenic activities.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Bioactive glasses; Biopolymers; Bone regeneration; Hybrids; Hydrogels